Bridging the Digital Divide: Understanding Technological Anxiety Toward AI in the Next Generation of IT Professionals - Melo, Bergson Gabriel da Silva Oliveira; Araújo, Vitor Meneghetti Ugulino de; Araujo, Ivo Crescencio de; Santos, Allejandro Sousa dos; Pinto, Pedro Henrique Ramos (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2025: Anais do VI Workshop sobre as Implicações da Computação na SociedadeDO - 10.5753/wics.2025.8556, 2025)
This study investigates the perception of AI-driven job displacement among computing students. Using a machine learning approach with psychometric data, the analysis identified key factors influencing students’ fear of replacement, including academic program, semester, learning strategies, and proficiency in using LLMs. Results show that students with less exposure to AI and those relying on memorization report higher anxiety, while those trained to develop and critically engage with GenAI tools exhibit more confidence. This work highlights the importance of curriculum design, AI literacy, and ethical reflection to prepare students for an AI-driven future.